FAKTOR-FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN PERTANIAN KE NON PERTANIAN DI KABUPATEN MINAHASA UTARA - Marla M. Mokoagow; Caroline B.D. Pakasi; Ellen G. Tangkere (COCOS, 2016)
ABSTRACTThis study aimed to analyze the factors influence the conversion of agriculture land to non agriculture in Northern Districts Minahasa. The variables analyzed were total population, the GDP per capita and the number of industries. Data used for ten years from 2005 to 2014. This research was conducted in December 2015 to January 2016, from preparation to preparation of the report. The data used are secondary data obtained from relevant agencies such as the Central Bureau of Statistics North Sulawesi, Northern Districts Minahasa and the Department of Agriculture of Northern Districts Minahasa. Secondary data were collected that the number of inhabitants, the GDP per capita and the number of Northern Districts Minahasa industry with the time series data (time series). Data analysis was performed using the Linear Regression Analysis. Analysis was performed twice. The results of multiple linear analysis first on a variable number of the population, the GDP per capita and the number of industries that don’t get a good result so needs to be re-done with respesifikasi models by removing one of the variables is the variable the GDP per capita. The results of multiple linear analysis after removing the GDP per capita variable indicates that the number of significant effect on the decline of land in Northern Districts Minahasa. The population continues to increase making the demand for real estate increasingly led to the development of the settlement require land that would utilize agricultural land, agricultural land resulting in a downward trend.Keywords : Northern Districts Minahasa, Conversion